The Baltic states of the Three Seas Initiative: Estonia, Latvia and Lithuania in creative relations with the United Arab Emirates - Krzymowski, Adam (Creativity Studies, 2022)
The presented manuscript deals with three Baltic states (Estonia, Latvia, and Lithuania) that are part of the Three Seas Initiative in the context of cooperation with the United Arab Emirates. The research’s goal is analysis the larger dimension of Three Seas Initiative and its creative role and importance in the international arena, including the Middle East. In this sense, this paper asks a research question of whether the relations between Estonia, Latvia, Lithuania, and the United Arab Emirates have the potential for deeper and broader creative dynamics of their cooperation. The presented article is the first research work of this type. Thus, it fills a gap in the literature and analyses concerning relations between the Baltic states and the United Arab Emirates. This work is primarily base on empirical research conducted for ten years. In addition, the author used his own creative experience, including as an Ambassador to the United Arab Emirates (2011–2015) or Senior advisor at Expo 2020 (2016–2018), responsible for strategies and creative development of relations the United Arab Emirates with all the Three Seas Initiative countries, including Baltic states. As a result of the research, the author argues that Estonia, Latvia, and Lithuania, as a part of the Three Seas Initiative, should make this concept more creative in its external dimension, with the United Arab Emirates. Expo 2020 (1 October, 2021–31 March, 2022) provides an opportunity for creative diplomacy. This event is an occasion to demonstrate joint projects, also in global aspects.